Design, Development, and Analysis of Combined Darrieus and Savonius Wind Turbine - Yadav, Pankaj; Joshi, Hem Raj; Bhattarai, Ashish; Bhatta, Bishnu; Neupane, Nabin (OODBODHAN, 2024)
This study concerns the design, development, and analysis of the combined Darrieus and Savonius wind turbine. The circumferential placement of three straight Darrieus blades with a NACA 0018 cross-section and a helically twisted Savonius blade ensures an even distribution of torque. Savonius can be used to self-start a wind turbine, something that the Darrieus cannot do on its own due to its unique design. All the wind turbine parts are designed using CAD software, and simulation data is obtained via the CFD approach. Also, the design is imported to FlashForge Finder to 3D print the wind turbine profile, and finally, testing is carried out. The plastic material used for Savonius is ABS, and that for Darrieus is PLA. Equipped with a hybrid design, the fabricated VAWT has exhibited notable characteristics during testing. Its cut-in wind speed, which is the minimum required for operation, is remarkably low, at 3 m/s. Under 6 m/s wind conditions, it achieves a maximum power output of 7.5537 watts. Additionally, the rotor blade has registered a peak rotational speed of 431 rpm at 6 m/s, showcasing its promising potential for wind energy harnessing. Furthermore, a graph plot analysis of the data collected from both processes reveals a comparable slope characteristic. Additionally, mechanical losses have been demonstrated by the discrepancy between the theoretical and experimental data. The study investigates the performance of a novel wind turbine model equipped with an innovative self-starting mechanism, eliminating reliance on external motors, across a range of wind velocities.